Effective-eigenvalue approach to the nonlinear Langevin equation for the Brownian motion in a tilted periodic potential: Application to the Josephson tunneling junction - COFFEY, WILLIAM THOMAS; KALYMYKOV, YURI PETROVICH (American Physical Society, 1993)
The effective-eigenvalue method is used for a calculation of the impedance of the Josephson tunneling junction for an externally applied small-signal alternating current in the presence of noise. The accuracy of the method is demonstrated by comparing the exact and approximate calculations. It shows clearly that the effective-eigenvalue method yields a simple and concise analytical description of the solution of the problem under consideration.
PUBLISHED
Keywords: Fluids and plasma physics